'Film as Sound Art: Embracing Love through Extra-diegetic Sound in Nadine Labaki's Caramel'. Issue 2 (2nd January 2022) - Sendra, Estrella
Abstract : Teaching film often involves un-learning previously taught histories of cinema to find instead 'herstories' (Dovey, 2018 ) and theirstories of cinema. This video essay constitutes an illustrative example of this practice, showing how Lebanese woman-led film Sukkar Banat/Caramel (Nadaine Labaki 2007 ) has been taught at SOAS, University of London to emphasise the crucial role of sound in narrative while rethinking the film canon and encouraging critical reflection on the gaze. By creatively compiling encounters between two characters in the film, the video essay shows two women gazing at each other in ways that evoke a romantic relationship, even if their contact stays in the hair salon. While there is barely any dialogue, the extra-diegetic music forges an intimate atmosphere. The decoding of these moments is shaped by the context of censorship in Lebanon, where explicit representations of same-sex relationships could be punished by law. In this video essay, I suggest that sound helps represent a queer gaze between the two characters, subverting both heteronormativity and patriarchal society, and in so doing, it also queers the audience's gaze. Caramel thus serves as an excellent case study of the possibilities of sound in film, and of film as sound art.